RECONSRUCTED CONSUMER IDEOLOGY BY TV SERİALS - Nesrin KULA DEMİR (Fırat University, 2019)
The early uses of the concept of “consume” means "to destroy, to spend, to waste, to finish". Today it is described as “to finish” and “the act of extravagance”. Consume can be taken as a term which is located in between the concepts of production and destruction. The concept of consumption has a meaning evolves through the conception such as to transform, to overcome, even the self destruction. Jean Baudrillard describes the consumption as a semiotic system that regulated through codes and rules. The new subjects of consumer culture make their way of consumption a life project, instead of accepting without thinking about it. By the way of bringing together their clothes, lifestyle practices, their appearance and their bodies, around this life project, they exhibited their own subjectivity and appreciation to others. Accordingly styles of consumption become an element of the people’s identity. The subjects use the commodities in order to express their identities and by the way becomes that the status of people in a community can only be measured through their consumption. TV series, also gives information to in